1969
DOI: 10.1111/j.1432-1033.1969.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of M and N Blood Group Glycoproteins and Glycopeptides with Alkaline Borohydride

Abstract: The sialic acid-free M and N substances and glycopeptides from their pronase digest were treated with alkaline borohydride and products of degradation were fractionated. Galactose and N-acetylgalactosamine were split off during the degradation in the form of disaccharide : galactosyl-N-acetylgalactosaminitol, and it was accompanied by the release of amino acid components. The conclusion has been drawn that a part of carbohydrate moiety of M and N substances represents trisaccharides: N-acetylneuraminyl-galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…[ 35] have shown that the polyagglutinable cell population has a diminuition or abolition of the receptor sites for MN-antibodies and the lectins from Vicia graminea and Arachis hypogoea which are directed against alkali labile NA and Gal, respectively [11,13,16,26,32,33].…”
Section: -Jv-acetylneuraminyl-(2-*-3)-/j-d-galactosyl-(l-*-3)-[a-7v-amentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35] have shown that the polyagglutinable cell population has a diminuition or abolition of the receptor sites for MN-antibodies and the lectins from Vicia graminea and Arachis hypogoea which are directed against alkali labile NA and Gal, respectively [11,13,16,26,32,33].…”
Section: -Jv-acetylneuraminyl-(2-*-3)-/j-d-galactosyl-(l-*-3)-[a-7v-amentioning
confidence: 99%
“…In Tn-syndrome a rare condition of acquired mixed field polyagglutinability with facultative hemolytic anemia, leucocytopenia and thrombocy topenia, a proportion of the red cells has a lowered sialic acid (NA) content and consequently a decreased electrophoretic mobility [ [26,37,38], the hypothesis was put forward that Tn-polyagglutinable erythro cytes have a deficiency of alkali-labile NA and galactose (Gal) [8], Experi mental evidence for this was obtained from the following observations : Tnantigen is uncovered by removal of NA and Gal from normal erythrocyte glycoproteins. Subsequent alkaline borohydride degradation in order to split off the peptide-linked GalNAc leads to a destruction of the receptor site.…”
Section: Introductionmentioning
confidence: 99%
“…The NV, activity is also confined to alkali-labile oligosaccharide chains [8], but is significantly enhanced after the release of sialic acid from the glycoproteins [14-161. The increase of Nvg activity on desialization of M and N antigens reached for both antigens a similar level.…”
mentioning
confidence: 99%
“…The alkalilabile oligosaccharides [4,8,20] with un changed sialic acid residues [4,5,7,9,14] are required for the reaction of M and N antigens with specific antisera. Chemical studies have not revealed, so far, any struc tural difference between M and N glyco proteins.…”
Section: Introductionmentioning
confidence: 99%